2006
DOI: 10.21273/hortsci.41.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lime Sulfur and Fish Oil on Pollen Tube Growth, Leaf Photosynthesis and Fruit Set in Apple

Abstract: The effect of liquid lime sulfur (LS) and fish oil (FO) application during bloom on leaf photosynthesis (Pn) and pollen tube growth in apple (Malus ×domestica) flowers were investigated in order to determine their mode of action as a bloom thinning agent. LS increased the percentage of flowers with fewer than 10 pollen tubes per flower to more than 64% compared to 5% or less in the control. Pollen tubes were completely absent from 27% to 48% of flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 11 publications
(12 reference statements)
1
23
1
Order By: Relevance
“…These results regarding the beneficial effects of fish oil on growth and fruiting of Ewaise mango are in harmony with (Olmo et al, 1981;Osnaya and Schlasser, 1998;Mc-Arthey et al, 2006;Yoder et al, 2009;Masoud and Abou-Zaid-Eman, 2017).…”
Section: -Effect Of Fish Oilsupporting
confidence: 79%
See 1 more Smart Citation
“…These results regarding the beneficial effects of fish oil on growth and fruiting of Ewaise mango are in harmony with (Olmo et al, 1981;Osnaya and Schlasser, 1998;Mc-Arthey et al, 2006;Yoder et al, 2009;Masoud and Abou-Zaid-Eman, 2017).…”
Section: -Effect Of Fish Oilsupporting
confidence: 79%
“…Using fish oils was responsible for promoting growth tree nutritional status, yield and fruit quality of different horticultural crops (Olma et al, 1981;Osnaya and Schlasser, 1998;Mc-Arthey et al, 2006;Yoder et al, 2009;Masoud and Abou-Zaid-Eman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Young spur apple leaves play a vital role in supplying the developing fruits with carbohydrates (Corelli Grappadelli, 2003) and in fruit retention (Ferree and Palmer, 1982). A reduction in Pn after application of caustic materials at bloom (McArtney et al, 2006;Noordijk and Schupp, 2003) or from shading or Pn inhibitors (Byers et al, 1990a(Byers et al, , 1990b has been suggested as a causal factor in fruit thinning (Byers, 2003). Injury to spur leaves or shading followed by reductions in Pn could reduce fruit size.…”
Section: Discussionmentioning
confidence: 99%
“…Dormant spray oils have been shown to reduce Pn in apple leaves (Ferree and Hall, 1975) and en-hance the thinning activity of mild chemical thinners . McArtney et al (2006) reported that liquid lime sulfur (LS) and fish oil applied at bloom time suppressed Pn and likely contributed to the thinning response of these materials.…”
mentioning
confidence: 99%
“…The female flower's acidic stigmatic secretions that facilitate pollen hydration and germination can also be damaged by alkaline dust (Sett, 2017). McArtney et al (2006) reported sulfur liming at bloom inhibited pollen tube growth and subsequently reduced fruit set in apple (Malus domestica).…”
mentioning
confidence: 99%